Therapeutic Plateletpheresis in Patients With Thrombocytosis: Gender, Hemoglobin Before Apheresis Significantly Affect Collection Efficiency - Jiang, Hongqiang; Jin, Yanxia; Shang, Yufeng; Yuan, Guolin; Liu, Dandan; Li, Jianfang; Wang, Cong; Ding, Lu; Tong, Xiqin; Guo, Shishang; Gong, Fayun; Zhou, Fuling (Frontiers in Medicine, 2021)
Background: Thrombocytosis is a common symptom in myeloproliferative neoplasms (MPN), and excessive proliferation may deteriorate into thrombosis, bleeding, myelofibrosis, and may ultimately convert to acute leukemia. This study aimed to investigate the collection efficiency of plateletpheresis (CEPP) and factors influencing its efficacy in patients with thrombocytosis. Materials and Methods: From September 2010 to December 2016, 81 patients from two institutions in China with myeloproliferative neoplasms and thrombocytosis accompanied by severe symptoms were treated with plateletpheresis by Fresenius COM. TEC machine. Results: After apheresis, the median CEPP was 20.71%(IQR:9.99%-36.69%) and median PLT reduction rate was 25.87%(IQR:21.78%-36.23%). Further analysis showed that no significant difference was observed between PLT count with 800–1000×109/L and >1000×109/L. The PLT counts significantly decreased (P<0.001) after plateletpheresis, the red blood cell (RBC), white blood cell (WBC), hemoglobin (HGB), and hematocrit (HCT) levels showed no significant differences before- or after- plateletpheresis. Multivariate analysis showed that female sex (P=0.009) and HGB (P=0.010) before apheresis were associated with CEPP. Female (P=0.022), HCT (P=0.001) and blood volume (P=0.015) were associated with the PLT reduction rate. Furthermore, symptoms were relieved after apheresis in patients whose PLT count was 800–1000×109/L accompanied with symptoms. Conclusions: It is reasonable to perform plateletpheresis when the PLT count is over 800×109/L and patients are complicated by clinical symptoms such as dizziness, headache, somnolence, and stupor. Plateletpheresis is effective in removing PLTs especially in females with high HGB.